Assessing Service Quality using SERVQUAL Model: Comparison of Public-Private Hospitals - Pun, Lal Bahadur (Butwal Campus Journal, 2021)
Patients’ perceptions of the services provided by a particular healthcare organization affects the image and profitability of the hospital and it also significantly affects the patient behavior in terms of their loyalty and word-of-mouth. The purpose of this paper was to measure the patients` expectations and perceptions and thereby compare them between private and public hospitals. Based on SERVQUAL model, self-administered questionnaire was prepared with six-point Likert-type scaled questions. Using judgemental sampling, the questionnaires were distributed to 450 patients at different locations of Butwal, out of which only 391 questionnaires were usable. The result revealed that private hospitals have been providing relatively better services than the public hospitals.